Characteristics of Hospitalized Patients Screening Positive for Delirium. (February 2020) - Nguyen, Trinh H.; Atayee, Rabia S.; Derry, Katrina L.; Hirst, Jeremy; Biondo, Anthony; Edmonds, Kyle P.
Background: Delirium in the hospitals leads to worse outcomes for patients. There were no previous studies that characterize patients with delirium from multiple hospital locations. Objective: To describe patient characteristics screening positive for delirium and identify any correlations with hospital location and medication use. Design, Settings, Patients: Retrospective chart review of 227 hospitalized patients from a large, academic, tertiary referral, 2-campus health system. Patients were ≥18 years old and had delirium for at least ≥24 hours. Validated delirium screening tools were utilized. Measurements: Patients' demographics, inpatient stay information, delirium episodes characteristics, drugs, and palliative and psychiatry teams' involvement. Results: Most patients were older with a mean age of 64.1 years. The most common primary diagnoses were infection, cardiac, and pulmonary. Average length of delirium was 7.2 days (standard deviation [SD] = 8.2), and average length of stay (LOS) was 18.7 days (median = 10.5, SD = 35.1, 95% confidence interval = 14.1-23). Thirty-day readmission rate was 24.8% (65/262 hospitalizations); 12.8% of patients died in the hospital (29/227). Around one-third of hospitalizations had involvement of palliative care, palliative psychiatry, or general psychiatry team. There was a decrease in the number of medications administered 24 hours after the first recording of delirium compared to the immediate preceding 48 hours. Those hospitalizations where delirium first occurred in the intensive care unit (ICU) did have a longer LOS (average = 22.9, SD = 45.7) than those where delirium first occurred outside the ICU (average = 14.8, SD = 20.5). Patients were likely to have received an opioid within 48 hours in 51% of hospitalizations and to have received benzodiazepines in 16% of hospitalizations. Conclusion: In our study, we found that delirium significantly impacted length of delirium episode, number of episodes of delirium, length of hospital admission, and mortality. The population most sensitive to the impacts of delirium were elderly patients.